MARKETING STRATEGY OF PIG FARMING ON UD. MOLEH FARM - F. A., Putra; Putri, B. R. T.; Sukanata, I W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the marketing strategy of pig livestock in UD. Moleh Farm. The research methods used are qualitative and quantitative. The selection of consumer respondents and experts used a stratified sampling method consisting of wholesalers, retailers, direct consumers, forecasters, academics and policyholders. The data sources used are premier data and secondary data. This research was conducted in Abiansemal District, Badung Regency, Bali Province from September to October 2021. The data analysis used is ife, EFE, IE, SWOT and QSPM matrix analysis. The results of the IFE matrix analysis with a total score of 2.48 and the total EFE matrix score of 2.08. The IE matrix gets the result of the position of the effort located in cell V which means it Hold and Maintain. Based on the results of the SWOT analysis and QSPM analysis, there are 7 strategies that are important to be applied in an effort to improve pig marketing at UD Moleh Farm, namely à strategies that have been prioritized based on QSPM analysis a) developing the market through increasing sales marketing; b) maintaining product quality by setting quality standards for pigs that are ready for sale to maintain customer loyalty; c) expanding marketing networks by promoting on social media; d) take part in livestock exchanges, livestock contests, and harvests on certain occasions; e) increase the application of biosecurity to suppress livestock disease outbreaks; f) diversifying products; and look for cheaper alternative feed sources without compromising the nutritional content of the  feed.